DFT study of the chemical reaction and physical properties of ibuprofen sodium. (13th August 2022) - Díaz Compañy, A.; Simonetti, S.
Abstract: In this paper, it is presented the chemical reaction of ibuprofen and sodium bicarbonate that gives the ibuprofen sodium as a product, using DFT calculations as a tool to study the activation energy and the free energy of the chemical reaction. The charge distribution, the density of states (DOS) and Infrared (IR) spectrum of the salt is presented. The chemical reactivity descriptors: ionization potential (I), electron affinity (A), electronegativity ( χ ), chemical potential (μ), hardness (η), softness ( s ) and electrophilicity (ω) index are calculated for all the species. A better knowledge of ibuprofen sodium will be a more and major uses for the salt for pharmaceutical and other applications. Graphical abstract: Image 1